Book PR: do readers influence on the communication of publishing company? - Tetiana Yezhyzhanska; Tetiana Krainikova; Larysa Masimova (Innovative Marketing)
The impact of readers as target audiences of publishing houses in Ukraine on PR communication is not clearly understood. The goal of this research is to examine the role of readers in the communication process between publishing houses and customers. The readers become an important source of information about the events of the book publishing market and book novelties. The article shows the results of the poll of visitors of the largest book festivals in Ukraine – Book Arsenal Festival in Kyiv and Book Forum in Lviv for 2017–2019. These respondents (200 interviews per event) are not only the main consumers of book products publishing houses, but also they are the source of information about new books and activities of Ukrainian publishing houses themselves. According to the results of the poll, visitors of book fairs pay attention to the advice of their colleagues and friends, which are an important source of information about the events of the book publishing market and book novelties. Almost 50% of respondents create and distribute user-generated content about the events of the book publishing market. This activity is explained by the lack of information about the book market news of more than half of visitors. The results of the research confirm that readers are important publishing communications subjects, consumers are active advocates of the publisher’s brand, friends and colleagues actively create the content about the events of the book publishing market in Ukraine.